Comparison of Acceleration Acting on Cargo in Front and in Rear Part of Semi-Trailer during Braking with and without Using the Systems ABS/EBS - Zamecnik, Jan; Jagelcak, Juraj; Sokjer-Peterssen, Sven (Communications - Scientific letters of the University of Zilina, 2016)
This article deals with braking tests of semi-trailer truck in forward and rear driving direction. It compares the accelerations and angular velocities in the front and rear part of the semi-trailer and their influence on forces in lashing points when using front lashing. The paper also contains a comparison between forces reached in the lashing points at the rate of cargo weight between the braking tests of semi-trailer and similar braking tests of a van. The first part of the paper contains also possibilities of using tracking devices for detecting accelerations acting on cargo in semi-trailer during transport.